Treatment of oil‐based drill cuttings by hydrophobic deep eutectic solvents. (18th August 2021) - Li, Jing; Jiao, Yanjun; Luo, Qin; Hu, Weixin; Fang, Shenwen; Tang, Chunling; Liu, Qiang
Abstract: During the exploitation of shale gas, there are many oil‐based drill cuttings (OBDC) produced, which are hazardous waste. In this paper, the characteristics of OBDC were analyzed and 25 hydrophobic deep eutectic solvents (DESs) were prepared as extractants for treating OBDC. The results showed that the DES formed by lauric acid and thymol had the highest extraction efficiency. The significant parameters of the extraction process were studied by using total petroleum hydrocarbon (TPH) as an index and the rational extraction conditions were recommended as follows: 0.8:1 mole ratio of lauric acid to thymol, 10:1 mass ratio of DES to OBDC, and 1 h extraction time at 60°C. The TPH of OBDC can be decreased from 14.75 to 0.87 wt.% at this recommended condition. The high extraction efficiency was also confirmed by energy dispersive spectrum results of treated OBDC. In addition, the lauric acid/thymol DES can be recycled and the TPH was still smaller than 1% after three cycles. This research suggests that hydrophobic DES extraction is an effective technology for TPH removal from OBDC. Abstract : Hydrophobic deep eutectic solvent (DES) used for oil‐based drill cuttings (OBDC) cleaning.